ANTI-BIO GRAM PROFILE IN THE SETTING OF A HIGH FREQUENCY OF MULTI-DRUG RESISTANT ORGANISMS AT DOCTORS HOSPITAL AND MEDICAL CENTRE, LAHORE, PAKISTAN - RIAZ , Z; RANA , AA; KHOSO , M; KHAN , MBA; REHMAN , SU; FARHAN , A (Biological and Clinical Sciences Research Journal, 2024)
Antimicrobial resistance (AMR) has emerged as a worldwide concern. The overuse and abuse of antibiotics pose a severe hazard to low-income nations in addition to reducing therapeutic choices. This is a retrospective cross-sectional study conducted at the Doctors Hospital and Medical Center surgical ICU in Lahore between January 1, 2021, and December 31, 2021. Three hundred sixty-four patients’ blood, tracheal, and urine culture data were gathered from patients hospitalized in the intensive care unit and processed by CLSI’s standard microbiological methods. Stanford University’s web-based anti-bio gram and CLSI were used to construct the anti-bio gram. The study examined 364 individuals, and the cultures that were taken from various places included the trachea (13%), urine (33%), and blood (54%). No organism has been identified from blood cultures thus far. Klebsiella (5), Acinetobacter (4), and Pseudomonas (3) were the most frequently isolated species from tracheal cultures and E. coli, with four isolates, followed by Klebsiella with three and Pseudomonas with two isolated from urine cultures. Staphylococcus sp. exhibited 100% resistance to vancomycin and linezolid. For both Acinetobacter and Klebsiella, colistin showed 100% resistance. E. coli was resistant to moxifloxacin (p value= 0.04). Since multidrug-resistant bacteria are often seen in intensive care units (ICUs), we must use caution when prescribing broad-spectrum antibiotics to avoid overtaxing weaker strains. Preventing the spread of resistant isolates in critical wards and preserving ICU patients will have advantageous outcomes.